Problem Severity, Technology Adoption, and Intent to Seek Online Counseling Among Overseas Filipino Workers - Hechanova, Ma. Regina (Archīum Ateneo, 2013)
This study examined the factors that influence the intent to seek online counseling among overseas Filipino workers (OFWs). A survey among 365 OFWs revealed that problem severity and technology adoption predict intent to use online counseling. Among the three factors of technology adoption, perceived ease in the use of technology and perceived presence of organization and technological infrastructure to support use predicted intent to use online counseling. Our hypothesis about the presence of interaction between problem severity and facilitating conditions was supported. Among individuals with low problem severity, those who perceive the presence of organization and technological infrastructure to support use have a higher intent to use online counseling. However, at higher levels of problem severity, the effect of facilitating conditions seems to disappear. These findings highlight the crucial role of preventive online mental health services. The study contributes to theory by integrating the stage model of help-seeking behaviors and technology adoption theory in predicting intent to use online counseling. Specifically, that intent to seek online counseling is affected by the existence and perceived gravity of a problem, moderated by technology adoption factors, particularly facilitating conditions. These have implications on the need to educate potential users on the advantages of counseling and ensure that migrant workers have access to technology and that the technology is easy to use.